Introduction of Robot-T at Baitul Hikmah Junior and Senior High School to Enhance Students' Learning Interest: Pengenalan Robot-T di SMP dan SMA Baitul Hikmah untuk Meningkatkan Minat Belajar Siswa - Susilawati, Helfy; Etnisa, Moch Mirza; Wiharso, Tri Arif; M.Angdarun, M.Angdarun; Sobari, Acep Hasan (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
The advancement of technology, accompanied by the development of artificial intelligence, has also led to significant progress in the field of robotics. Robotics is an appealing subject because it combines physical forms with control mechanisms. However, unlike in large urban areas, robotics remains a rare subject taught in schools located in smaller, more remote regions. One such example is Baitul Hikmah Junior and Senior High School, located in the Tarogong Kaler district, where robotics has not yet been introduced into the curriculum. Therefore, this community service initiative focuses on introducing Robot-T to the students of Baitul Hikmah Junior and Senior High School. The primary goal of this program is to familiarize students with robotics, starting with the design and operational mechanisms of the pre-designed Robot-T. The results of this community service show that the students were highly enthusiastic about the introduction of Robot-T, as evidenced by their active participation throughout the socialization process